Analisis Kesalahan Siswa dalam Menyelesaikan Soal Sharing Task dan Jumping Task Berdasarkan Kriteria Watson - Murtikusuma, Randi Pratama; Hobri, Hobri; Pratiwi, Cikal Citra (Edumatica : Jurnal Pendidikan Matematika, 2022)
The purpose of this research is to know and identify student's errors in solving problems of sharing task and jumping task on social arithmetic material based on Watson's criteria in terms of DISC personality type. The research is descriptive qualitative. Data collection is obtained from sharing task, jumping task, test DISC personality type, and interview. Subject in this research are class VIIIF Junior High School 4 Jember which consisted of 12 students with details of 12 students to work on sharing task and 8 students to work on jumping task. Based on the result of this research is dominance, influence, steadiness, and compliance personality types all make mistakes, namely Innapropriate Procedure/IP, Response Level Conflict/RLC and Skill Hierarchy Problems/SHP. Then for Undirected Manipulation/UM, the personality types are dominance, influence, and steadiness. Influence, steadiness, and compliance personality types also perform Innapropriate Data/ ID and Above Other/ AO errors. Finally, the steadiness personality type makes mistakes, namely Omitted Data / OD.